2019
DOI: 10.31557/apjcp.2019.20.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Abnormalities in Multiple Myeloma Patients at a Tertiary Healthcare Center in India

Abstract: Objective: Multiple myeloma (MM) is a clinically and genetically heterogeneous plasma cell neoplasm. The prognosis of MM patients is dependent on several factors including the patient’s age, the stage of disease and genetic alterations. This study aimed to determine the frequency of common chromosomal abnormalities and their significance in MM patients referred to a tertiary healthcare center in India. Methods: Fluorescence in situ hybridization on interphase nuclei fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…1 The overall frequency (22.2%) observed in this study was higher than that reported by other studies from Western India (10-15%). 13,14 Deletion 17p is known to acquire during the course of progression of the disease and is more common to occur in relapsed/refractory setting. Lakshman et al 15 reported acquisition of del 17p at a median of 35.6 months of diagnosis after a median of two lines of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 The overall frequency (22.2%) observed in this study was higher than that reported by other studies from Western India (10-15%). 13,14 Deletion 17p is known to acquire during the course of progression of the disease and is more common to occur in relapsed/refractory setting. Lakshman et al 15 reported acquisition of del 17p at a median of 35.6 months of diagnosis after a median of two lines of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The various centers observed frequencies ranging from 33.3 to 74.9%. 10 11 12 13 These studies differed in their results as the range of CAs selected for testing was highly variable and so was the method used for cytogenetic study (FISH only/FISH and conventional CG/CG only). The studies that included ploidy level along with immunoglobulin heavy-chain (IgH) translocations reported higher incidence rates of CAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 Metaphase analysis by G banding provides us with a tool to detect aberrations at the cellular level in 30–50% of patients in advanced stages than in cases with newly diagnosed MM. 3 In patients with a low proliferative index, the identification of cryptic anomalies is better detected by interphase fluorescence in situ hybridization (iFISH) than by conventional cytogenetics (CCs). iFISH is a more sensitive method as this technique can facilitate detection on a cell-by-cell basis using region-specific probes.…”
Section: Introductionmentioning
confidence: 99%